ANALISIS KUALITAS LAYANAN DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN - Rena Eka Setyawati; Muinah Fadhilah; Ambar Lukitaningsih (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
This study aims to determine (1) the influence of service quality on purchasing decisions (2) the influence of brand image on purchasing decisions (3) the influence of purchasing decisions on consumer satisfaction (4) the influence of service quality on consumer satisfaction (5) the influence of brand image on consumer satisfaction. The sample in this study was Lazada users in Yogyakarta since 2020. The data collection method uses a questionnaire method that is shared using the Accidental Purposive Sampling technique. In this study, Indicator test, Hypothesis Test, Path Analysis and Dominant Factor Analysis were used using SmartPLS 3.2.9. The results of this study show that (1) service quality has a positive and significant effect on purchasing decisions (2) brand image has a negative and insignificant effect on purchasing decisions (3) purchasing decisions have a positive and significant effect on consumer satisfaction (4) service quality has a positive and significant effect on consumer satisfaction (5) brand image has a negative and insignificant effect on consumer satisfaction.